Child and caregiver mental health during 12 months of the COVID-19 pandemic in Australia: findings from national repeated cross-sectional surveys. Issue 1 (28th July 2022) - Price, Anna MH; Measey, Mary-Anne; Hoq, Monsurul; Rhodes, Anthea; Goldfeld, Sharon
Abstract : Background: There are calls for research into the mental health consequences of living through the COVID-19 pandemic. Australia's initial, effective suppression of COVID-19 offers insights into these indirect impacts in the relative absence of the disease. We aimed to describe the mental health experiences of Australian caregivers and children over 12 months, reporting differences related to demographic, socioeconomic and lockdown characteristics. Methods: Data were from Australia's only nationally representative, repeated cross-sectional survey of caregivers with children (0–17 years). N=2020 caregivers participated in June 2020, N=1434 in September 2020 and N=2508 in July 2021. Caregivers reported their mental health (poor vs not, Kessler-6), and perceived impacts of the pandemic on theirs and their children's mental health (negative vs none/positive). Data were weighted to approximate population distributions of caregiver age, gender, sole caregiving, number and ages of children, state/territory and neighbourhood-level disadvantage. Results: Perceived impacts on mental health were more frequently negative for female (vs male) caregivers and older (vs younger) children. Poor caregiver mental health (Kessler-6) was more common for families experiencing socioeconomic adversity (especially financial), while perceived impacts were more frequently negative for more socially advantaged groups. Caregivers who experienced the least total lockdown reported similar mental health over time. Otherwise, poor mental health and perceived negative impacts increased over time with increasing total length of lockdown. Conclusion: Despite Australia's low infection rates, the negative mental health experiences of the COVID-19 pandemic are real and concerning. Addressing poor mental health must be central to ongoing pandemic recovery efforts for families and children.